Le mythe comme fondement des territoires et de l’ordre social dans les îles de l’ouest de Sumatra (Indonésie) - Dominique Guillaud (EchoGéo, 2008)
This paper recalls some avenues of research that J. Bonnemaison explored in the field of cultural geography: the relations between myth and territory, the way in which political relationships are inscribed into space and land boundaries, and the role of “geosymbols” as memorials for political and social systems. This demonstration is inspired by the works that Bonnemaison carried out on a privileged field, the archipelago of Vanuatu; the paper explores the same kind of correspondences between political and spatial order in two Indonesian island, Nias and Siberut, and tries to reveal the strategic dimension invested in myths and narratives of foundation.